Efeito da β-amilase e α-amilase fúngica seguido de desramificação na formação e características estruturais de amido resistente tipo 3 de batata e araruta - Villas Boas, Flávia [UNESP] (2014)
Resistant starch (RS) is defined as the fraction of starch that does not suffer from the action of digestive enzymes from the gastrointestinal tract showing a similar behavior to that of dietary fiber. Retrograded starch, defined as RS3, is composed mainly of amylose and debranched starch due to its greater tendency to reassociation. In this work the effect of β-amylase and fungalα-amylase on the formation and physicochemical properties of RS3 from potato and arrowroot starches were investigated. Starch suspensions (6,5%w/v) werefirst gelatinized and then hydrolyzed by β-amylase (400U/g) or fungal α-amylase (5U/g potato starch, 10U/g arrowroot starch) for 6h. Aliquots of the supernatant were collected and hydrolysis degree was determined by measuring total carbohydrate content (phenol−sulfuric method).The hydrolysates were debranched by pullulanase (40U/g), for 10h, cooled to 4°C for 16h to enhance the retrogradation, precipitated using ethanol, and dried. Control samples were produced from the gelatinization and debranching of the starch without the use of amylase. The retrograded starches were characterized for molecular weight distribution of starch components (GPC), amylopectin branched-chain length distribution (HPAEC-PAD), crystalline pattern (X-ray diffraction), thermal properties (DSC) and RS content. The amylolysis of potato and arrowroot starches resulted in a similar hydrolysis degree (~25%) independent of used enzymes. Native potato starch displayed type B crystalline pattern, 10,7% of amylose,and a high proportion of long branch chains of amylopectin (DP≥37) while arrowroot starch displayed type A crystalline pattern, 19,5% of amylose, and a high proportion of short branch chains (DP 6-12). The action of β-amylase resulted in both starches significant increase in the proportion of chains with DP 25-36 and significant reduction in chains with DP 13-24, while the fungal α-amylase...